Discovery of disubstituted xylylene derivatives as small molecule direct inhibitors of Keap1-Nrf2 protein-protein interaction. Issue 6 (15th March 2020) - Abed, Dhulfiqar Ali; Lee, Sumi; Hu, Longqin
Graphical abstract: Abstract: The Keap1–Nrf2–ARE system represents a crucial antioxidant defense mechanism that protects cells against reactive oxygen species. Targeting Keap1–Nrf2 protein–protein interaction (PPI) has become a promising drug target for several oxidative stress-related and inflammatory diseases including pulmonary fibrosis, chronic obstructive pulmonary disorder (COPD) and cancer chemoprevention. For the development of a potential therapeutic agent, drug-like properties and potency are important considerations. In this work, we focused on the modification of 4 as a lead through a molecular dissection strategy in an effort to improve its metabolic stability, leading to the discovery of a series of new disubstituted xylylene derivatives. The preliminary SAR of 9a indicated that compound 21a containing S -methylated acetate moieties exhibited comparable potency to the lead compound 4 in a fluorescent polarization assay but with improved metabolic stability in the presence of human liver microsomes.